Zwanzig Jahre Völkerstrafgesetzbuch Anwendungspraxis und Reformbedarf - Jeßberger, Florian; Epik, Aziz (Schriften zum Internationalen und Europäischen Strafrecht, 2023)
Two decades of the "Völkerstrafgesetzbuch" provide an occasion for a critical reflection and a discussion of possible needs for reform in substantive and procedural law. The volume contains contributions from representatives of the judiciary, the legal profession, civil society and academia to the symposium "20 Jahre Völkerstrafgesetzbuch", which took place in October 2022 at the University of Hamburg. In this volume, the editors have brought together the relevant voices on "German International Criminal Law". The authors paint a balanced picture of the practice of prosecuting crimes under international law in Germany and offer numerous suggestions for legislators and practitioners from different perspectives. With contributions by Dr. Tanja Altunjan | Prof. Dr. Stefanie Bock | Prof. Dr. Boris Burghardt | Dr. Anne Dienelt | Anna-Julia Egger | Prof. Dr. Aziz Epik | Dr. Peter Frank | Antonia Gillhaus | Duscha Gmel | Merle Iffert | Prof. Dr. Florian Jeßberger | Wolfgang Kaleck | Dr. Patrick Kroker | Prof. Dr. Dr. Milan Kuhli | Prof. Dr. Chantal Meloni | Prof. Dr. Stefan Oeter | Prof. Dr. Tilman Repgen | Nella Sayatz | Prof. Dr. Jürgen Schäfer | Andreas Schüller | Prof. Dr. Leonie Steinl.